Cultivated ties and strategic communication: Do international environmental secretariats tailor information to increase their bureaucratic reputation? - Saerbeck, B. (2022)
The past few years have witnessed a growing interest among scholars and policy-makers in the interplay of international bureaucracies with civil society organizations, other non-profit entities, and the private sector. This article extends the state of research by investigating whether and how secretariats try to strengthen their reputation within their respective policy regimes through information provision and alliance building. Based on reputation theory, the article argues that ties cultivated with stakeholders as well as appearance and presentation of information are decisive in this regard. Methodologically, the study implements a mixed-methods design that combines a quantitative survey with social network analysis and qualitative content analysis of interviews with stakeholders within the climate and biodiversity regime. We show that the secretariats of the Convention on Biological Diversity (CBD) and the United Nations Framework Convention on Climate Change (UNFCCC) maintain relationships with a wide range of state and non-state actors to enhance their reputation. Moreover, different types of actors receive different types of information from the two secretariats studied. Our findings reveal that both secretariats use their limited resources for investing strategically into networks with different types of actors (in the broader transnational policy network), either via the tailored provision of information or through strategic networking with multipliers. They also indicate that reputation does not simply depend on characteristics of bureaucracies, but also on framework conditions and different communication strategies.